“Nós podemos reinventar o mundo”: a concepção da história para Paulo Freire - Loureiro, Camila Wolpato (Universidade do Vale do Rio dos Sinos, 2024)
In this research, we problematize and identify Paulo Freire's perception of the concept of History, understanding its propositions for a project, an intentionally counter-hegemonic pedagogical policy, to build a more just and equal world. To do this, we start with the following problem: to what extent Paulo Freire developed an original conception of History, and how are his interviews part of this proposal? To answer this, we use the theoretical reference of descoloniality, highlighting how the subordination of Latin American subjects is a historical process of dehumanization, and how the author's experience and positions are related to this perception. As research sources, we draw on a robust documentary corpus, through interviews given by Paulo Freire to the Brazilian press, between 1979 and 1997, a period that includes the return of his period in exile from Brazil, until the year of his demise. As a research methodology, we carried out a quantitative and qualitative analysis of themes, debates, and speeches present in Freire's speeches and editorials, based on documentary analysis of a historiographical nature. In addition to the interviews, we carried out the crossing of these data with the dense analysis of three works by the author: Pedagogy of the Oppressed (1987), Pedagogy of Hope: Reliving Pedagogy of Oppressed (1992), and Pedagogy of Freedom (2002). Through the theoretical framework of descoloniality, together with methodological curation, it was possible to realize that Paulo Freire established an original conception of History. For the author, History is the understanding of the past-present-future three-dimensionality as a hopeful process of searching for the humanization of historically oppressed subjects. This conception is evidenced through a close look at his epistemology, both in the works mentioned, as well as documentary sources, which allowed us to verify his speeches beyond the books, in their relationship with the press and their interlocutors. Furthermore, an analysis undertaken in this investigation discovered Freire's trajectory as a man of his time, understanding his experiences, ruptures, and contradictions as part of building his knowledge and understanding of History.

En esta investigación problematizamos e identificamos la percepción de Paulo Freire sobre el concepto de Historia, entendiendo sus propuestas para un proyecto político pedagógico intencionalmente contrahegemónico, con el objetivo de construir un mundo más justo e igualitario. Para eso, partimos del siguiente problema: en ¿En qué medida Paulo Freire desarrolló una concepción original de la Historia y ¿ cómo sus entrevistas son parte de esta propuesta? Para que sean respondidas, utilizamos el marco teórico de la descolonialidad, destacando cómo en la subalternización los sujetos latinoamericanos son un proceso histórico de deshumanización, y cómo la experiencia y posiciones del autor están relacionadas con esta percepción. Como fuentes de investigación, utilizamos un corpus documental robusto, a través de entrevistas concedidas por Paulo Freire a la prensa brasileña, entre 1979 y 1997, período que incluye el regreso del período de exilio de Brasil, el año de su muerte. Como metodología de investigación se realizó un análisis cuantitativo y calidad de temas, debates y discursos presentes en los discursos de Freire y en dos editoriales, para a partir de un análisis documental de carácter historiográfico. Además de entrevistas, realizamos el cruce de estos datos con un denso análisis de tres obras del autor: Pedagogia del Oprimido (1987), Pedagogía de la Esperanza: un reencuentro con la Pedagogía del Oprimido (1992) y Pedagogía de la Autonomía (2002). A través del marco teórico descolonialidad, junto con el curador metodológico, se pudo dar cuenta de que Paulo Freire establece una concepción original de la Historia. Para el autor, la Historia es la comprensión de la tridimensionalidad pasado-presente-futuro como un proceso esperanzador de búsqueda de la humanización de sujetos históricamente oprimidos. Esta concepción es evidenciada a través de una mirada cercana a su epistemología, tanto en los trabajos citados, cuánto documenta en las fuentes, lo que le permitirá comprobar sus discursos para todos libros, en su relación con la prensa y sus interlocutores. Además, el análisis realizado en esta investigación permitió comprender la carrera de Freire como hombre de su tiempo, entendiendo sus vivencias, rupturas y contradicciones como parte de la construcción de su conocimiento y comprensión de la Historia.
Keywords: Paulo Freire; História; Fontes documentais; History; Documentary sources; Historia; Fuentes documentales; ACCNPQ::Ciências Humanas::Educação